2003
DOI: 10.1177/073953290302400115
|View full text |Cite
|
Sign up to set email alerts
|

Television Exposure Not Predictive of Terrorism Fear

Abstract: This study of university undergraduates examined the role of television coverage of terrorism in perpetuating fright and fear following the Sept. 11 attacks. Viewer characteristics, rather than television exposure, were the most consistent predictors of fear, safety and faith in others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Her findings suggest that such images do raise anxiety levels, and also that anger and fear are significantly related to risk estimates and policy preferences. Rubin et al (2003) examined cultivation effects of television exposure on fear of terrorism and whether individual-level differences (i.e., locus of control, victimization experience, and gender) could explain the relationship between media consumption and fear of terrorism. Results indicated that the effect of overall television exposure and terrorism-related television exposure had no effect on fear of terrorism; however, motivation for viewing was significantly related to fear of terrorism.…”
Section: Media Exposure and Fearmentioning
confidence: 99%
“…Her findings suggest that such images do raise anxiety levels, and also that anger and fear are significantly related to risk estimates and policy preferences. Rubin et al (2003) examined cultivation effects of television exposure on fear of terrorism and whether individual-level differences (i.e., locus of control, victimization experience, and gender) could explain the relationship between media consumption and fear of terrorism. Results indicated that the effect of overall television exposure and terrorism-related television exposure had no effect on fear of terrorism; however, motivation for viewing was significantly related to fear of terrorism.…”
Section: Media Exposure and Fearmentioning
confidence: 99%
“…Attending to real graphic media coverage may serve to exacerbate fear, especially when it depicts random and senseless killings. For example, research conducted in the wake of the 9/11 attacks found that being exposed to terrorism-related stories (Rubin et al, 2003) and watching 3 hr or more of 9/11 coverage daily (Holman & Silver, 2005) was associated with increased fear of being victimized by terrorists. Ultimately, terrorists seek to instill widespread fear and anxiety (Silver & Matthew, 2008) and show that their actions are justified (Winkler, El Damanhoury, Dicker, & Lemieux, 2018) against those with whom they are fighting (O’Neil & Gray, 2011).…”
mentioning
confidence: 99%
“…21 However, other researchers, on the grounds of the data of public opinion polls conducted in the USA, did not establish that watching TV news covering the topic of terrorism could significantly affect the fear perceived by people. 22 It is obvious that the external validity of these two studies is debatable; social experiences in terms of terrorism in both Israel and the USA are unique. On the other hand, these and similar studies have revealed that assessments of military threats are affected by both the socio-demographic characteristics of the individual and the individual's sense of self-efficacy.…”
Section: Overview Of the Researchmentioning
confidence: 99%